2015
DOI: 10.1371/journal.pone.0139992
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Phytotoxicity Assessment of Phenolic Compounds in Chrysanthemoides monilifera subsp. monilifera (Boneseed)

Abstract: Chrysanthemoides monilifera subsp. monilifera (boneseed), a weed of national significance in Australia, threatens indigenous species and crop production through allelopathy. We aimed to identify phenolic compounds produced by boneseed and to assess their phytotoxicity on native species. Phenolic compounds in water and methanol extracts, and in decomposed litter-mediated soil leachate were identified using HPLC, and phytotoxicity of identified phenolics was assessed (repeatedly) through a standard germination b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…Research on canola suggested that the synergistic effect of sinapyl alcohol, p-hydroxybenzoic and 3,5,6,7,8-pentahydroxy flavones played a role for canola allelopathy against annual ryegrass (Asaduzzaman et al 2015). Research on boneseed's allelopathy indicated that the mixture of ferulic acid, catechin, phloridzin and pcoumaric acid showed a stronger inhibiting effect on Isotoma axillaris compared to individual phenolics (Al Harun et al 2015). The combined allelopathic effect of three allelochemicals of Chara vulgaris also expressed Data is the average values with standard errors of the replicates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on canola suggested that the synergistic effect of sinapyl alcohol, p-hydroxybenzoic and 3,5,6,7,8-pentahydroxy flavones played a role for canola allelopathy against annual ryegrass (Asaduzzaman et al 2015). Research on boneseed's allelopathy indicated that the mixture of ferulic acid, catechin, phloridzin and pcoumaric acid showed a stronger inhibiting effect on Isotoma axillaris compared to individual phenolics (Al Harun et al 2015). The combined allelopathic effect of three allelochemicals of Chara vulgaris also expressed Data is the average values with standard errors of the replicates.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing compounds (like ketones, alkaloids, terpenes) were reported as potential allelochemicals of other plants (Guo et al 2015;Kato-Noguchi et al 2011;Ma et al 2009). Interestingly, the growth inhibitory activity of some potential allelochemicals was much greater than that of phenolic acids (Kato-Noguchi et al 2012), and some compounds presented a synergistic effect when exhibiting their allelopathic effect (Al Harun et al 2015;Zhang et al 2012;Zuo et al 2015). In previous studies, the polar compounds in ethyl acetate extraction of R. glutinosa leaves and fibrous roots have been preliminary analysed for the identification of allelochemicals (Li et al 2012;Wang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect was more pronounced in CH3OH extracts of A. inulifolium, where polar compounds are commonly found. Methanolic extracts of some plant species were known to contain phenolics and other toxic substances (Belicova et al, 2001;Al Harun et al, 2015). These phenolics may inhibit the germination process through their interference in the indole acetic acid metabolism, or synthesis of protein and Some bioactivities of Austroeupatorium inulifolium 97 iron uptake by plants (Blum, 1998;Castro et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Severe inhibition of germination of Isotoma axillaris was described to be due to ferulic acid, catechin, phloridzin, and p-coumaric acid generated by boneseed (Chrysanthemoides monilifera subsp. monilifera) litter [38]. Long-term cultivation of lemon balm was shown to accumulate phenolics in the soil and exert phytotoxic effects on the growth and the essential oil yield [39].…”
Section: Effect Of O-cresol On Seed Germinationmentioning
confidence: 99%